GEOCRONOLOGIA Rb/Sr E K/Ar NO ENXAME DE DIQUES MÁFICOS DE UAUÁ, BAHIA (BRASIL) - Bastos Leal, L. R.; Teixeira, W.; Piccirillo, E. M.; Leal, A. B. Menezes; Girardi, V. A. V. (Geochimica Brasiliensis, 2011)